Pemberian Bawang Merah terhadap Demam pada Bayi - Veronica, Septika Yani; Yane, Ade; Sakdiah , Anita; Komalasari, Komalasari (Ners Akademika, 2023)
Purpose: The Infant Mortality Rate (AKB) shows that neonatal health services in a country are not good. (Ministry of Health, 2017). Baby health problems are one of the main problems in the field of health. Fever is a condition of an increase in body temperature above normal. This covetous obstetric care that focuses on the upbringing of babies is by providing onion compress interventions in feverish babies aimed at reducing fever in infants. Research Methodology: This study is a case study with the subjects of 3 babies who had a fever, the intervention was given on day 1 of fever until day 3. Result: The results of the study were obtained from 3 babies who had a fever by being given onion compress interventions to experience a decrease in temperature on day 1 to day 3. It can be concluded that shallots are effective against a decrease in body temperature in feverish toddlers. For health workers, in order to be able to cooperate with Puskesmas in creating an evidence-based care program for mothers who have babies and toddlers that can increase maternal understanding so that they can apply complementary therapy onion compresses as an alternative herbal medicine that can reduce body temperature in newborns and toddlers with fever.